Polityka migracyjna 'bez polityki': Antynomie tworzenia polityki migracyjnej w polsce w okresie 2016-2022 - Sławomir Łodziński; Marek Szonert (University of Warsaw, Centre of Migration Research (CMR), 2023)
– The article focuses on the analysis of the evolution of work on Polish migration policy in the period 2016-2022. The first date is set by events related to the migration crisis in Europe (and its political reception in Poland) and the official withdrawal from the state's migration policy program adopted in 2012. The second date is set by the humanitarian crisis on the PolishBelarusian border (occurring since August 2021 until today, although now with less intensity) and the effects of the war in Ukraine and the reception of war refugees from this country in Poland. At that time, the migration status of our country changed from a typical emigration country to an emigration and immigration country, mainly due to economic migrations based on the dominance of short-term and circular migrations (mainly from Ukraine). In the article, we draw attention to the fundamental importance of the lack of clear goals of the state's migration policy and the lack of rules for their implementation. This mainly concerned the failure to reach a compromise between the goals related to the interests of the economy and the demographic needs of the society and the narrowly understood priorities of maintaining state security. This gave rise to both internal competition between individual institutions within the central administration, and was conducive to high political sensitivity of work on developing the program of this policy. Its effect was that the state's migration policy took on the character of a public policy without politics, i.e. consistent actions in various fields of migration (such as the labor market, Polish diaspora policy, border protection and refugee policy) without a broader political and an official discussion about its long-term goals. This situation was also conducive to the emergence of antinomies in its functioning consisting in the gap between the proclaimed slogans of security and the actual course of migration, leading to "unintentional consequences" in its functioning (Adamczyk 2021).
Keywords: 330; migration policy; new institutionalism; model of “ garbage policy” institutional bricolage; Poland